Evidencias de estandarización en la manufactura de cuencos de la Aguada Orilla Norte (Argentina) - Balesta, Bárbara (2009)
In this paper we analyze a representative sample of the funerary vessels belonging to the Aguada culture (Northwest Argentina), recovered in excavations performed in the Aguada Orilla Norte cemetery, in Hualfin Valley, during the 1920s. It aims to provide evidence on the standardization of this kind of pottery, and its relationship with productive specialization in an unequal society.